Common measure of quality of life for people with systemic sclerosis across seven European countries: a cross-sectional study. Issue 7 (20th February 2018) - Ndosi, Mwidimi; Alcacer-Pitarch, Begonya; Allanore, Yannick; del Galdo, Francesco; Frerix, Marc; García-Díaz, Sílvia; Hesselstrand, Roger; Kendall, Christine; Matucci-Cerinic, Marco; Mueller-Ladner, Ulf; Sandqvist, Gunnel; Torrente-Segarra, Vicenç; et al.
Abstract : Objectives: The aim of this study was to adapt the Systemic Sclerosis Quality of Life Questionnaire (SScQoL) into six European cultures and validate it as a common measure of quality of life in systemic sclerosis (SSc). Methods: This was a seven-country (Germany, France, Italy, Poland, Spain, Sweden and UK) cross-sectional study. A forward–backward translation process was used to adapt the English SScQoL into target languages. SScQoL was completed by patients with SSc, then data were validated against the Rasch model. To correct local response dependency, items were grouped into the following subscales: function, emotion, sleep, social and pain and reanalysed for fit to the model, unidimensionality and cross-cultural equivalence. Results: The adaptation of the SScQoL was seamless in all countries except Germany. Cross-cultural validation included 1080 patients with a mean age 58.0 years (SD 13.9) and 87% were women. Local dependency was evident in individual country data. Grouping items into testlets corrected the local dependency in most country specific data. Fit to the model, reliability and unidimensionality was achieved in six-country data after cross-cultural adjustment for Italy in the social subscale. The SScQoL was then calibrated into an interval level scale. Conclusion: The individual SScQoL items have translated well into five languages and overall, the scale maintained its construct validity, working well as a five-subscale questionnaire. Measures of quality of life in SSc can be directly compared across five countries (France, Poland Spain, Sweden and UK). Data from Italy are also comparable with the other five countries although require an adjustment.